2018
DOI: 10.1136/bmjopen-2018-024938
|View full text |Cite
|
Sign up to set email alerts
|

Age, health and other factors associated with return to work for those engaging with a welfare-to-work initiative: a cohort study of administrative data from the UK’s Work Programme

Abstract: ObjectivesTo investigate the role of individual factors (including age, health and personal circumstances) and external factors associated with clients having a job start while engaging with the Work Programme and variations by benefit type.SettingThe UK Government’s main return to work initiative (The Work Programme) in Scotland.DesignPiecewise Poisson regression to calculate incident rate ratios using administrative data from 2013 to 2016 to identify factors associated with job start.Participants4322 Employm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Many qualitative studies have shown that entering paid employment is often challenging for persons with mental health problems (10,11). Some quantitative studies also have shown that persons with psychological or physical health conditions have lower likelihood of entering paid employment (12)(13)(14)(15). Less is known about the influence of having a specific chronic disease or multiple chronic diseases on entering paid employment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Many qualitative studies have shown that entering paid employment is often challenging for persons with mental health problems (10,11). Some quantitative studies also have shown that persons with psychological or physical health conditions have lower likelihood of entering paid employment (12)(13)(14)(15). Less is known about the influence of having a specific chronic disease or multiple chronic diseases on entering paid employment.…”
mentioning
confidence: 99%
“…In fact, multimorbidity – the occurrence of at least two chronic diseases within an individual – has been associated with a higher risk of unemployment ( 16 ). One study showed that unemployed individuals with two health conditions had a 24% decreased likelihood of entering paid employment compared to those with no health conditions ( 14 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Health issues have, therefore, received special attention with respect to interventions promoting work participation [1,[17][18][19][20]. Previous studies have indicated that health also influences outcomes of interventions that are not primarily health-related, such as in active labour market programmes [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Social networks have been found to be influential in job searching and eventual labour market outcomes by researchers, such as Granovetter (1973Granovetter ( , 1995, Kramarz and Skans (2014), Mowbray et al (2018) and Brown et al (2018). Lin (2001) suggested a positive influence of networks in that they allow the social capital of others to be accessed, which can be mobilised to supply job related information or more actively help in securing employment by providing references or advocating to employers.…”
Section: Introductionmentioning
confidence: 99%